a)2x + 1 = 16b) 6 -3x =12 - 6x c) 2/3 X (3x - 6) = 20d) 4 X (x - 1) = 6 X ( x + 1)e) 12 - 5x + 1 = 15 - 3x
a) 2x + 1 = 16
16 - 1 = 15
15 : 2 = 7,5
czyli: 2 x 7,5 + 1 = 16
a) 2x+1=16
2x=16 - 1
2x=15 /2
x=15/2= 7 1.2
b) 6 - 3x=12 - 6x
-3x+6x=12-6
3x=6 /3
x=2
c) 2/3 X (3x-6)=20
mnożymy: 6/3x - 12/3=20
2x - 4=20
2x= 24 /2
x=12
d) 4 X (x - 1)=6 X (x + 1)
4x - 4=6x + 6
4x - 6x= 6 + 4
-2x= 10 /(-2)
x=-5
e) 12 - 5x + 1= 15 - 3x
-5x + 3x= 15 - 12 - 1
-2x= 2 /(-2)
x=-1
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a) 2x + 1 = 16
16 - 1 = 15
15 : 2 = 7,5
czyli: 2 x 7,5 + 1 = 16
a) 2x+1=16
2x=16 - 1
2x=15 /2
x=15/2= 7 1.2
b) 6 - 3x=12 - 6x
-3x+6x=12-6
3x=6 /3
x=2
c) 2/3 X (3x-6)=20
mnożymy: 6/3x - 12/3=20
2x - 4=20
2x= 24 /2
x=12
d) 4 X (x - 1)=6 X (x + 1)
4x - 4=6x + 6
4x - 6x= 6 + 4
-2x= 10 /(-2)
x=-5
e) 12 - 5x + 1= 15 - 3x
-5x + 3x= 15 - 12 - 1
-2x= 2 /(-2)
x=-1